Biotecnological war conceptual evaluation tool for the biotechnology and protein chemistry teaching for undergraduate and postgraduate students in biological sciences - Toyama, Marcos Hikari [UNESP]; Gaeta, Henrique Hessel [UNESP]; Ortolan, Bruna Doimi [UNESP]; Bittencourt Rodrigues, Caroline Fabri [UNESP]; Costa, Caroline Ramos da Cruz [UNESP]; Belchor, Mariana Novo [UNESP]; Toyama, Daniela de Oliveira (Soc Brasileira Bioquimica & Biologia Molecular, 2017)
Biochemistry in general is practically unanimous as a discipline with a high degree of difficulty, complex and boring. So, practical and creative play games as teaching methodology has been disseminated in several disciplines of biological sciences. Biotecnological war board game is a proposal that was initially conceived as an alternative complementary tool for biochemistry teaching of proteins and peptides, challenging students, aiming to review concepts transmitted in classroom, stimulating student's abilities, such as their creativity, competitiveness, resource management and making possible to correlate biochemistry importance of proteins and peptides as new products. This game proved to be an excellent tool for complementary evaluation of students, which besides stimulating teamwork, also stimulated a strong competitive spirit within the classroom, which allowed to analyze students' perception in relation to the theme and mainly articulated group work.
Keywords: Didactic game; protein chemistry; biotechnology